Pemberdayaan Komunitas dalam Peningkatan Ekonomi Pasca Fenomena Kekeringan pada Sektor Pertanian di Gampong Manyang Baroh, Aceh Utara - Muhammad Nasiruddin; Mursyidin Mursyidin; Zani Al Farid; Ruhmi Arini; Meri Meri; Nadia Nadia (Universitas Teuku Umar, 2025)
Manyang baroh Village in North Aceh experienced the impact of long-term drought which caused a decrease in agricultural production and community income, especially rice farmers. To overcome this, community empowerment was carried out through various methods such as observation, identification of needs, entrepreneurship training, land conversion, and development of MSMEs. The results found showed an increase in household income of up to 30%, increased skills, and strengthening social networks and awareness of local potential. This program also succeeded in improving the community's economy and strengthening village community solidarity after the drought. The methods used in this program include long-term observation, identification of community needs, entrepreneurship training, conversion of non-productive land to productive land, and development of Micro, Small, and Medium Enterprises (MSMEs). This program encourages collaboration between students and local residents through discussions, surveys, and interviews to coordinate activities that are in line with the long-term needs of the community.